Activated protein C ameliorates coagulopathy but does not influence outcome in lethal H1N1 influenza: a controlled laboratory study - Schouten, Marcel; van der Sluijs, Koenraad F; Gerlitz, Bruce; Grinnell, Brian W; Roelofs, Joris JTH; Levi, Marcel M; van 't Veer, Cornelis; Poll, Tom van der (Critical care (London, England), 2010)
Introduction Influenza accounts for 5 to 10% of community-acquired pneumonias and is a major cause of mortality. Sterile and bacterial lung injuries are associated with procoagulant and inflammatory derangements in the lungs. Activated protein C (APC) is an anticoagulant with anti-inflammatory properties that exert beneficial effects in models of lung injury. We determined the impact of lethal influenza A (H1N1) infection on systemic and pulmonary coagulation and inflammation, and the effect of recombinant mouse (rm-) APC hereon. Methods Male C57BL/6 mice were intranasally infected with a lethal dose of a mouse adapted influenza A (H1N1) strain. Treatment with rm-APC (125 μg intraperitoneally every eight hours for a maximum of three days) or vehicle was initiated 24 hours after infection. Mice were euthanized 48 or 96 hours after infection, or observed for up to nine days. Results Lethal H1N1 influenza resulted in systemic and pulmonary activation of coagulation, as reflected by elevated plasma and lung levels of thrombin-antithrombin complexes and fibrin degradation products. These procoagulant changes were accompanied by inhibition of the fibrinolytic response due to enhanced release of plasminogen activator inhibitor type-1. Rm-APC strongly inhibited coagulation activation in both plasma and lungs, and partially reversed the inhibition of fibrinolysis. Rm-APC temporarily reduced pulmonary viral loads, but did not impact on lung inflammation or survival. Conclusions Lethal influenza induces procoagulant and antifibrinolytic changes in the lung which can be partially prevented by rm-APC treatment.